2009
DOI: 10.1007/s10979-008-9140-1
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and social control of probationers with co-occurring mental and substance abuse problems.

Abstract: Probationers with co-occurring mental and substance abuse problems (PCPs) are both subject to considerable social control, and at high risk of probation failure. In this study, we screened 601 probationers for symptoms, interviewed 82 identified PCPs about their relationships, and then followed these PCPs for eight months to record treatment nonadherence and other probation violations. First, PCPs' social networks were small, heavily comprised of professionals and opposing forces who engaged in risky behavior,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
110
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(132 citation statements)
references
References 57 publications
10
110
1
Order By: Relevance
“…However, the link between youth-officer relationships as change mechanism and probation outcomes is less understood relative to offending adults (see Skeem, Eno Louden, Manchak, Vidal, & Haddad, 2009; Johnson, Friedmann, Green, Harrington, & Taxman, 2011; Kennealy, Skeem, Manchak, & Eno Louden, 2012). Research on offending adults suggests that three models of adult probation supervision and decision making differentially emphasize the two components of client-officer relationships (Klockars, 1972; Skeem & Manchak, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, the link between youth-officer relationships as change mechanism and probation outcomes is less understood relative to offending adults (see Skeem, Eno Louden, Manchak, Vidal, & Haddad, 2009; Johnson, Friedmann, Green, Harrington, & Taxman, 2011; Kennealy, Skeem, Manchak, & Eno Louden, 2012). Research on offending adults suggests that three models of adult probation supervision and decision making differentially emphasize the two components of client-officer relationships (Klockars, 1972; Skeem & Manchak, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Supporting this idea, four studies (Bui & Morash, 2010;Cobbina, 2010;Morash, 2010;Skeem, Eno Louden, Manchak, Vidal, & Haddad, 2009) in different states found that parole agents constitute important members of social networks for many women offenders. Yet another study (Bloom, Owen, Covington, & Raeder, 2003) found that, compared to men, women on parole were especially likely to be open about their needs, put more value on their relationships with parole agents, and develop more trusting relationships with them.…”
Section: Influence Of Memorable Messages On Female Offenders As Suggementioning
confidence: 97%
“…After release from prison or forensic psychiatric hospitals, many end up homeless and unemployed, with small social networks (Hartwell, 2004;McNiel, Binder, & Robinson, 2005;Skeem, Louden, Manchak, Vidal, & Haddad, 2009). In addition, many show functional impairment (Grella, Greenwell, Prendergast, Sacks, & Melnick, 2008), and suffer from victimization (Wood, 2012) as well as from problematic substance use and mental health problems (Proctor & Hoffman, 2012;Ruiz, Douglas, Edens, Nikolova, & Lilienfeld, 2012).…”
Section: Introductionmentioning
confidence: 99%